Makna Pendampingan Persalinan Berbasis Masyarakat (MPPBM) pada Kader Kesehatan di Wilayah Kerja Puskesmas Baloi Permai - Susanti Susanti; Silvia Mona; Ana Faizah (Pusat Riset dan Inovasi Nasional, 2024)
Community-based childbirth assistance (MPPBM) is an important approach in efforts to reduce maternal and infant mortality rates. Health cadres have a strategic role in assisting pregnant women and facilitating referrals to health facilities. This study aims to explore the knowledge and meaning of health cadres related to community-based childbirth assistance. This study used a qualitative approach with a descriptive phenomenological design involving 8 cadres in the Baloi Permai Health Center work area. Data were collected through in-depth interviews and analyzed using the Colaizzi phenomenological analysis method. The results showed five main themes that describe the knowledge and meaning of assistance according to cadres: Assistance as a form of social concern, Knowledge of pregnancy danger signs and referrals, Assistance as a form of spiritual and emotional service, Challenges in carrying out the role as a companion, and Expectations for health system support. These findings can be used to improve the quality of cadre training and strengthen community-based assistance policies.